Effect of Chlorpyrifos Insecticide on Hatchability and Larva Survival of Silver Rasbora (Rasbora argyrotaenia) - Putri, Dewi Aurina Sukirno; Latuconsina, Husain; Lisminingsih, Ratna Djuniwati (Agrikan Jurnal Agribisnis Perikanan, 2024)
The use of insecticides as pest control is one of the efforts of Indonesian farmers in increasing agricultural productivity. Chlorpyrifos insecticide is one type of organophosphate insecticide that is toxic and can have a negative impact on the environment. The study aimed to compare the effect of exposure to Chlorpyrifos insecticide with different concentrations on egg hatchability and larval survival of silver rasbora (Rasbora argyrotaenia). Experimental research with a completely randomized design (CRP). One way ANOVA to compare between treatments then further tested using DMRT (Duncan's Multiple Range Test), and larval mortality was analyzed using probit analysis. The results showed that different concentrations of chlorpyrifos insecticide had a significantly different effect on hatchability and survival of silver rasbora larvae (Rasbora argyrotaenia). The lethal concentration (LC50) of chlorpyrifos insecticide that can affect the hatchability and survival of silver rasbora larvae is 0.62 ppm. The results of this study provide valuable information for various parties related to the dangers of excessive use of insecticides because they can have a negative impact on the acute environment.